ISLAMIC FINANCING FOR RENEWABLE ENERGY IN INDONESIA: UNLOCKING POTENTIAL DEMAND FROM GCC INVESTORS - Kasri, Rahmatina A.; Rulindo, Ronald; Sakti, Muhammad Rizky Prima; Rifqi, Muhammad; Yuniar, Adela Miranti (Journal of Islamic Monetary Economics and Finance, 2024)
This study examines the interest of Gulf Cooperation Council (GCC) investors in financing renewable energy (RE) projects in Indonesia using Islamic financing schemes. It employs a multi-criteria decision-making (MCDM) method and Analytical Hierarchy Process (AHP) model with expert respondents representing institutional investors from the GCC states. To validate and enrich the analysis, it also conducted Focus Group Discussion and additional interviews with industry players and Indonesian regulators. The main finding indicates that the return on investment is the most crucial factor in selecting appropriate RE projects, followed by risk and impact of the projects. Furthermore, while the GCC investors do not have sufficient knowledge about the potential and sources of RE in Indonesia, they consider the solar panel project as most preferable. Next, the study finds investment return, Shariah compliance and liquidity as the main criteria in choosing Islamic financing instruments, where equity-based are the most preferred instrument, followed by asset-backed securities and blended financing instruments. In addition, tax incentives, cross subsidy and feed-in-tariffs are the most preferred incentives needed by the investors. The additional interviews that we conducted further affirm these findings. The results are expected to provide insights for the Indonesian policy makers, particularly fiscal and financial/monetary authorities, and the GCC investors to invest in Indonesia for financing RE projects using Islamic financing schemes. Acknowledgment We gratefully acknowledge the support provided by Universitas Indonesia Research Grant. The grant facilitated the research presented in this paper, allowing us to conduct data collection and analysis as well as disseminate our findings to a wider audience.